Characterization of the rumen lipidome and microbiome of steers fed a diet supplemented with flax and echium oil. Issue 2 (16th September 2014) - Huws, Sharon Ann; Kim, Eun Jun; Cameron, Simon J. S.; Girdwood, Susan E.; Davies, Lynfa; Tweed, John; Vallin, Hannah; Scollan, Nigel David
Summary Developing novel strategies for improving the fatty acid composition of ruminant products relies upon increasing our understanding of rumen bacterial lipid metabolism. This study investigated whether flax or echium oil supplementation of steer diets could alter the rumen fatty acids and change the microbiome. Six Hereford × Friesian steers were offered grass silage/sugar beet pulp only (GS), or GS supplemented either with flax oil (GSF) or echium oil (GSE) at 3% kg−1 silage dry matter in a 3 × 3 replicated Latin square design with 21‐day periods with rumen samples taken on day 21 for the analyses of the fatty acids and microbiome. Flax oil supplementation of steer diets increased the intake of polyunsaturated fatty acids, but a substantial degree of rumen biohydrogenation was seen. Likewise, echium oil supplementation of steer diets resulted in increased intake of 18:4n‐3, but this was substantially biohydrogenated within the rumen. Microbiome pyrosequences showed that 50% of the bacterial genera were core to all diets (found at least once under each dietary intervention), with 19.10%, 5.460% and 12.02% being unique to the rumen microbiota of steers fed GS, GSF and GSE respectively. Higher 16S rDNA sequence abundance of the genera Butyrivibrio, Howardella, Oribacterium, Pseudobutyrivibrio and Roseburia was seen post flax feeding. Higher 16S rDNA abundance of the genus Succinovibrio and Roseburia was seen post echium feeding. The role of these bacteria in biohydrogenation now requires further study.